Rare Earth Elements Recycling Potential Estimate Based on End-of-Life NdFeB Permanent Magnets from Mobile Phones and Hard Disk Drives in Brazil - Daniel Dotto München (MDPI AG, 2021)
Besides neodymium, the chemical composition of Neodymium–Iron–Boron (NdFeB) permanent magnets possibly contains other rare earth elements (REEs) such as praseodymium, dysprosium, and terbium. Among its applications, NdFeB magnets are essential for Hard Disk Drives (HDDs) in computers for data storage, in Mobile Phones (MPs), and in acoustic transducers. Because REEs were classified as critical raw materials by the European Union and the USA, the recycling of them has become an important strategy to diminish supply risk. Therefore, in this publication, the authors have uncovered the recycling potential estimate (RPE) of these four REEs from both end-of-life (EoL) secondary sources. The results were based on the time-step method, using in-use stock and sales data from Brazil over the last decade (2010–2019). Moreover, the NdFeB magnets were characterized by content and weight to a more accurate RPE. The EoL generation over the decade studied showed different scenarios for MPs and HDDs, mainly due to lifespan, social behavior regarding storage and usage, and resources. Under those circumstances, the RPE revealed 211.30 t of REEs that could return as raw materials in the last decade, of which approximately 80% is neodymium. Unfortunately, recycling rates are still too low, even more so in Brazil, which is problematic for the future REE supply chain and electronic waste figures.